Pediatric urological malignancies operated at a tertiary cancer center in Nepal: a 5 year experience - Pradhan, Sulav; Nepal, Umesh; Pokharel, Bharat Mani; Gharti, Binod Babu; Pokharel, Gyan Prasad; Lamichhane, Nirmal (Nepalese Journal of Cancer, 2023)
Introduction: Pediatric tumor is often an incidental discovery. Improvements in diagnosis modality and treatment have decreased the mortality rates.Materials and Method: We performed a retrospective review of pediatric patients operated in the Department of Urology at B.P. Koirala Memorial Cancer Hospital from January 2018 to December 2022.Results: A total of 28 pediatric patients were operated for cancers in that time duration. Among them there were 6 cases of Neuroblastoma, 19 cases of Nephroblastoma and 3 cases of Testicular germ cell tumors.Conclusion: Despite limited resources, a fair number of pediatric tumors are being managed in BPKMCH with good results.